Why are SMEs willing to pay trade zakat? Evidence from East Java, Indonesia - Rohman, Ghifary Duyufur; Al-Shaghdari, Fahd (Center for Islamic Economics and Development Studies [P3EI], 2025)
Purpose – This study aims to identify and analyze the key determinants influencing small and medium-sized enterprises (SMEs) compliance with trade zakat obligations in East Java, where zakat collection from the SME sector remains relatively low despite its socioeconomic potential.Methodology – This study adopts a quantitative approach utilizing Structural Equation Modelling (SEM) to analyze data collected through a structured questionnaire distributed to SME owners in East Java. In total, 171 valid responses were obtained. The six variables examined included entrepreneurs’ attitude, zakat literacy, role of zakat administrators, length of business, profitability, religiosity, and zakat.Findings – The results show that zakat administrators have a significant positive influence on SMEs’ willingness to pay zakat, whereas religiosity, zakat literacy, and entrepreneurs’ attitudes do not significantly affect willingness to pay. Additionally, religiosity, zakat administrators, and length of business significantly affected zakat literacy among SME owners.Implications – The findings highlight the strategic role of zakat administrators in promoting zakat compliance. Strengthening institutional roles and outreach programs can help increase zakat literacy and willingness to pay among SMEs, contributing to more effective zakat collection and socioeconomic development.Originality – This study contributes to the limited empirical literature on trade zakat compliance among SMEs in Indonesia by examining institutional and behavioral factors using a structured SEM approach. This underscores the need to shift focus toward institutional effectiveness rather than solely on individual religiosity or awareness.